Textile and Fashion Systems and the Sustainable Development Goals: A Narrative Review of Sustainability Pathways in Ghana - Edward Apau; Benjamin Tawiah; Charles Frimpong; Ebenezer Kofi Howard (Bina Nusantara University, 2026)
The textile and fashion industry plays a significant role in sustainable development due to its economic contributions, cultural relevance, and environmental implications. Despite growing scholarly attention to sustainability within the sector, limited research has systematically examined its relationship with the Sustainable Development Goals (SDGs), particularly in developing-country contexts. This study investigates how textile and fashion systems contribute to the SDG agenda, with a specific emphasis on Ghana. Adopting a narrative review methodology supported by a structured desk-based literature review, the study synthesises interdisciplinary scholarship on indigenous textile knowledge systems, sustainable production practices, circular economy strategies, labour conditions, and technological innovation. The review suggests that Ghana’s textile and fashion sector aligns with multiple SDGs, particularly SDGs 6, 8, 9, 12, and 13, through contributions to employment generation, cultural heritage preservation, resource-conscious production practices, and emerging innovation initiatives. However, the literature indicates that the sector’s sustainability potential is constrained by limited technological capacity, inadequate access to finance, weak institutional support, and increasing competition from imported textiles. The review further demonstrates that existing scholarship rarely positions textile and fashion systems explicitly within the SDG framework, resulting in a fragmented understanding of their sustainability contributions. This study contributes to the literature by providing an integrated SDG-based analytical framework for interpreting Ghana’s textile and fashion sector, synthesising environmental, economic, cultural, and innovation dimensions that are often examined separately within existing scholarship.